PENINGKATAN KEMANDIRIAN MELALUI METODE DEMONSTRASI ANAK USIA 5-6 TAHUN - (F54210019), Hartini; Thamrin, M.; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research is a from of action research with descriptive methods. Subjects were children of 20 children. Based on the research that has been done and through the results obtained after the analysis of the data held that : 1) Planning learning to increase self-sufficiency through method demonstration on children can be categorized as excellent, while the planning has been done teachers include: Formulating learning objectives, choose a theme, choose the main ingredient , determine methods pembelajran, making assessment of learning outcomes. 2) Implementation of learning to increase self-sufficiency through demonstration method in children aged 5-6 years can be categorized as